Composition and spatial distribution of metals and sulfur in urban roadside dust in Cancun, Mexico. Issue 3 (29th March 2021) - Hernández-Terrones, Laura; Ayala-Godoy, Jairo A.; Guerrero, Eugenio; Varelas-Hernández, Gerardo H.; Sánchez-Toriz, Denisse G.; Flores-Moreno, Mara F.; Pech-Perera, Cinthia B.
Abstract: The study investigated the concentration of metals (Cd, Cr, Cu, Ni, Pb, and Zn) and S in urban dust samples of Cancun, Quintana Roo, Mexico. This is the first study about urban dust pollution in Cancun. Urban dust samples were collected and divided in three groups: high traffic densities (HT), low traffic densities (LT), and fixed sources (FS). A statistical analysis was performed using Pearson correlation, Principal Component Analysis, and k-means clustering, in order to classify the data according to each sampling site. The behaviour of the corresponding concentration distributions is shown in cartographic data using Geographic Information Systems. Results from highest to lowest concentration, are as follows: S > Zn > Pb > Cu > Cr > Ni > Cd. Concentrations were compared with NOM-147-SEMARNAT/SSA1-2004, USEPA guidelines, and atmospheric fallout in topsoil estimated by 100 years of accumulation. Almost all results meet the norm NOM-147-SEMARNAT/SSA1-2004 limit, and USEPA guideline, except Cr (two sites) and Pb (three sites). However, results at all sites are higher than the atmospheric fallout limit. The geo-accumulation index (I-geo) class presents the order: Pb > Cu > Cd > Zn > S>Cr > Ni. The research revealed that urban dust from sites with heavy traffic had the highest S, Zn and Pb concentrations, while sites considered as low traffic and fixed sources showed significantly high levels of S, Cr and Pb. The results indicate two major sources contributing to metals and sulfur in road dust: (1) traffic and emissions from vehicles, and (2) vehicular parts. Finally, the results reported in this work could be useful to the authorities in order to select priority sites to install emissions monitoring systems.